Drug Development Targeting the Glycogen Synthase Kinase-3β (GSK-3β)-Mediated Signal Transduction Pathway: The Role of GSK-3β in the Maintenance of Steady-State Levels of Insulin Receptor Signaling Molecules and Nav1.7 Sodium Channel in Adrenal Chromaffin Cells - Takayuki Nemoto; Toshihiko Yanagita; Tasuku Kanai; Akihiko Wada (Elsevier, 2009)
Glycogen synthase kinase-3 (GSK-3) is constitutively active in nonstimulated cells, where the majority of its substrates undergo inactivation/proteolysis by phosphorylation. Extracellular stimuli (e.g., insulin) catalyze inhibitory Ser9-phosphorylation of GSK-3β, turning on signaling and causing other biological consequences otherwise constitutively suppressed by GSK-3β. Regulated and dysregulated activities of GSK-3β are pivotal to health, disease, and therapeutics (e.g., insulin resistance, neurodegeneration, tumorigenesis, inflammation); however, the underlying mechanisms of multifunctional GSK-3β remain elusive. In cultured bovine adrenal chromaffin cells, 1) constitutive and negatively-regulated activities of GSK-3β up- and down-regulated insulin receptor, insulin receptor substrate-1 (IRS-1), IRS-2, and Akt levels via controlling proteasomal degradation and protein synthesis; 2) nicotinic receptor/protein kinase C-α (PKC-α) / extracellular signal-regulated kinase (ERK) pathway up-regulated IRS-1 and IRS-2 levels, enhancing insulin-induced the phosphoiNOSitide 3-kinase (PI3K) / Akt / GSK-3β pathway; 3) inhibition of calcineurin by cyclosporin A or FK506 down-regulated IRS-2 level, attenuating insulin-like growth factor-I (IGF-I)-induced ERK and GSK-3β pathways; and 4) insulin, IGF-I or therapeutics (e.g., lithium) up-regulated the voltage-dependent Nav1.7 sodium channel. Keywords:: glycogen synthase kinase-3β (GSK-3β), LiCl, insulin receptor substrates-1 and -2, Nav1.7 sodium channel, adrenal chromaffin cell